Company Liability Towards Workers Who Are Dismissed During the Covid-19 Pandemic as A Force Majeure Circumstance - Rosandra Nabila Nugraha; Agus Mulya Karsona; Sherly Ayuna Putri (Dinasti Research, 2025)
The COVID-19 pandemic has significantly impacted the economy worldwide, including Indonesia. In the face of economic difficulties caused by social restrictions and declining demand, many companies have been forced to lay off employees as a last resort to maintain business continuity. This situation is often categorized as Force Majeure, an extraordinary event that cannot be predicted or avoided. Even though termination of employment can be carried out in these situations, applicable laws and regulations must still fulfill workers' rights. This study aims to determine the limitations of the COVID-19 pandemic as a Force Majeure situation and the company's responsibility towards workers laid off during the pandemic. The research method used is normative juridical, which is legal research on positive legal norms, principles, and doctrines with analytical descriptive research specifications that describe the applicable laws and regulations associated with legal theory and the practice of implementing positive law, which are then collected and classified into an orderly and systematic description. The study results show that the COVID-19 pandemic can be considered an urgent or Force Majeure, and companies are relieved to fulfill workers' rights. Still, many companies unilaterally layoff their workers. Protection of workers in these conditions is essential to prevent injustice and ensure social justice for the parties involved